Analisis Kepatuhan Wajib Pajak Umkm Terkait Pemberian Insentif Pajak PMK 86 Tahun 2020 Saat Pandemi di KPP Tasikmalaya - Luvita Putri Febriani Hakim; Arry Irawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
The compliance of MSME taxpayers at KPP Pratama Tasikmalaya in paying taxes during this pandemic is quite high, seen from the amount of MSME tax receipts for the period after the provision of the PMK tax incentive Number 86 of 2020 reached Rp. 4,112,051,290 and before the provision of tax incentives of Rp. 3,528,688,028. Compliance to register also increased significantly before the provision of incentives for 9793 registered MSME taxpayers, but after the provision of tax incentives, MSME taxpayers increased by 0.6%. This study aims to determine whether the provision of tax incentives for PMK Number 86 of 2020 can increase taxpayer compliance. This study uses a comparative approach with a sample consisting of MSME taxpayers at KPP Pratama Tasikmalaya. The type of data collected is quantitative data. the data source used is secondary data. Data collection techniques using documentation and analyzed by Kolmogorov Smirnov test, descriptive statistics and Paired sample t-test using the SPSS program. The results of this study indicate that the provision of tax incentives for PMK Number 86 of 2020 can increase taxpayer compliance. Judging from the results, there are differences in MSME compliance in the form of paying taxes and registering between before and after the provision of tax incentives for PMK Number 86 of 2020